Peran Budaya Organisasi dan Komitmen Organisasi Untuk Meningkatkan Kinerja Karyawan di RSU Muhammadiyah Ponorogo - Farida, Umi; Pransiska, Widiya Belle (BISNIS, 2019)
This research aims to determine the role of organizational culture and organizational commitment to improve employee performance at Muhamadiyah Ponorogo Hospital. There are several factors to improve employee performance, one of them is the organizational culture and organizational commitment which is well implemented according to hospital policy. Muhammadiyah general hospital as a research location with a number of respondents 105 employees with the technique used namely purposive sampling. Multiple regression analysis as a data analysis technique used to determine the role of organizational culture and organizational commitment to improve employee performance both partially and simultaneously. The results of the study show that organizational culture has a role in improving employee performance and organizational commitment also has a role on employee performance individually, while together organizational culture and organizational commitment have a role on employee performance, while the two variables are the most dominant its role is organizational commitment.